STREPTOMYCETES BIOLOGICAL PROPERTIES AND TAXONOMICAL STRUCTURE FROM NATURAL SOILS AND TECHNOZEMS OF KRYVYI RIG AREA - О. В. Сищикова (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2014)
Aim to select the streptomycetes from technogenic-disturbed and natural soils of Kryvyi Rig area, to establish their taxonomical structure, to carry out their identification and to assess the structure of the streptomycetes community. Methods. Allocation of streptomycetes pure culture performed on starch-ammonia agar. Identification of streptomycetes isolates was performed by 36 diagnostic signs using H.F. Hauze guidelines actinomycetes determinant, the description of the genus Streptomyces and computer program of their identification StmId, developed by the employees of Institute of Microbiology and Virology, National Academy of Sciences of Ukraine. Results. There were carried out the identification of bacterial strains based on morphological, cultural and physiological-biochemical properties. According to the morphology of spores 63.8% of surveyed cultures with smooth surface of spores, 24.1% – with thorns, 8.6% – with hillocks. The most streptomycetes isolated from soil have direct sporophores located monopodial. On the scale of colors of A.S. Bondartsev there were established that on mineral agar of Gauze-1 the amount of isolates with white and grey air mycelium made on 29%. For substrate mycelium of many isolates the shades of brown color are characteristic. Among the selected strains of microorganisms of 40% are capable to formation of soluble pigments 64% – melanoid. It is established that practically all isolates well grow on medium with glucose and sucrose. The least suitable for bacterial growth is medium with xylose. It is determined that the process of desamination of amino acids to form ammonia carry 64% of the studied cultures, and the cleavage of sulfur-containing amino acids to form hydrogen sulfide are able 57% of isolates. All studied cultures exhibit amylolytic, cellulolytic and proteolytic activity with varying intensity. Conclusions. The specific structure of streptomycetes community from technogenic-disturbed and natural soils of Kryvyi Rig area is established. It is determined that S. violaceomaculatus, S. sporoherbeus, S. aerionidulus, S. enduracidicus and S. grisinus prevailed in streptomycetes cenosis of natural soils whereas in the technozems – S. dayalbaghensis, S. sporostellatus, S. conganensis, S. violobrunneus and S. albocrustosus.